Music, Motor Control and the Brain - Altenmüller, Eckart; Wiesendanger, Mario; Kesselring, Jurg (Oxford Oxford University Press, 2006)
The motor actions that can be witnessed as a virtuoso musician performs can be so fast, so accomplished, so precise, as to seem somehow superhuman. The musician has to produce the movements, monitor those they have already made and the subsequent result, co-ordinate their hands, fingers, eyes, and perhaps throat and diaphragm. These achievements are of course the product of hundreds, even thousands of hours of practice — playing scales, studies, time and time again. But those hours of practice by no means guarantee that great musicianship will result. This technical prowess has to be combined with a range of other, perhaps, less tangible qualities. This book explores the secrets of musical virtuosity. It presents a comprehensive account of music and motor cognition, examining the neural basis of music making — our understanding of which is just starting to be enhanced by brain imaging. It considers the effect on our brains of prolonged music making. It explores the motor processes across a range of instruments (vocal, string, wind, percussion) and within different performance situations. It also considers what happens when things start to go wrong — why motor problems occur in so many professional musicians in later life, and the possible therapies for such problems. This book features contributions from leading psychologists, neuroscientists, and neurologists.This book explores the secrets of musical virtuosity. It presents a comprehensive account of music and motor cognition, examining the neural basis of music making - our understanding of which is just starting to be enhanced by brain imaging. It considers the effect on our brains of prolonged music making. It explores the motor processes across a range of instruments (vocal, string, wind, percussion) and within different performance situations. It also considers what happens when things start to go wrong - why motor problems occur in so many professional musicians in later life, and the possible therapies for such problems.Music is a topic of considerable interest within the brain sciences. With contributions from leading psychologists, neuroscientists, and neurologists, this book makes a unique contribution to our understanding of music and the brain.